Tinjauan Literatur Model Problem Based Learning (PBL) dan Implikasinya terhadap Hasil Belajar Siswa Madrasah Ibtidaiyah - Jumrah; Syahru Ramadhan; Abdul Haris; Ilham (Mataram University, 2026)
21st-century learning demands innovative learning models that develop students' critical thinking skills, character, and collaborative abilities. In the context of Islamic elementary education, Problem-Based Learning (PBL ) is considered relevant for improving learning outcomes while instilling Islamic values. This study aims to analyze the implementation of PBL in Islamic elementary schools (Madrasah Ibtidaiyah), the variety of models used, the supporting and inhibiting factors, and their impact on student and teaching outcomes. The study employed a literature review with a descriptive qualitative approach. Data were obtained from scientific journals, books, research reports, and policy documents relevant to the research topic. Data were then analyzed through data categorization, synthesis, and triangulation. The analysis shows that the implementation of PBL improves students' higher-order thinking skills, including analysis, evaluation, and synthesis of information, as well as increasing learning motivation, active participation, collaboration, and character development through the internalization of Islamic values, responsibility, tolerance, and empathy. In addition to its impact on students, the implementation of PBL also impacts all aspects of the teaching staff, particularly in improving pedagogical competence, creativity in lesson design, classroom management skills, skills in guiding student discussions and collaboration, and teacher readiness to implement innovative, student-centered learning models. The success of PBL implementation is influenced by teacher readiness, the availability of facilities and infrastructure, a conducive learning environment, and school institutional support. The conclusion of this study indicates that PBL is effectively implemented in Madrasah Ibtidaiyah because it not only improves student learning outcomes cognitively, affectively, and psychomotorically but also supports the professional development of teachers. Therefore, this study recommends ongoing training for teachers related to PBL implementation, the provision of adequate learning facilities, and the strengthening of school policies to support innovative, problem-solving-based learning.